Pengaruh Perceived Value terhadap Kepuasan dan Minat Beli Ulang Pelanggan Pasar Umum Ubud - Putri Anggreni (Telaah Bisnis, 2016)
Abstract As the foundation of economic and micro enterprises, traditional markets are increasingly replaced by modern market that intensively rushed into the countryside. To be competitive, small businesses in the traditional market needs to learn the management of marketing and consumer behavior, in the hope that customers will remain loyal to the product offered. The purpose of this study is to analyze the effect of perceived value toward customer’s satisfaction and repeat buying intention at the Ubud Traditional Market. The data have been analyzed by using Structural Equation Modeling (SEM) with the aid of a computer program Analysis of Moment Structure (AMOS). Sampling was taken by non-probability sampling, especially using the purposive and convenience sampling techniques. The study was conducted in December 2013 up to July 2014 involved for about 152 respondents. The results showed that the influence of perceived value to customer’s satisfaction is positive with a coefficient of 0.382, the effect of perceived value toward customer’s repeat buying intention is also positive with a coefficient of 0.129, and the influence of customer’s satisfaction toward customers repeat buying intention is positive as well, with a coefficient of 0.620. With these results, management was advised to have a better understanding of consumer behavior, customer’s satisfaction, and customer buying intention in traditional market.